Aplicación de la gestión de riesgos en forma oportuna para mejorar el desempeño de los proyectos de construcción - GOMEZ SANCHEZ SOTO, RUBEN (LACCEI, 2025)
Abstract– This study examines the importance of timely implementation of risk management in construction and infrastructure projects. The research identifies the planning and design phase, specifically during the preparation of the technical file, as the optimal time to initiate risk management. It demonstrates that this early implementation facilitates preventive actions, optimizes design, and establishes anticipatory response strategies, reducing costs and execution timeframes. The analysis reveals that the cost of implementing risk management ranges between 2.71% and 8.67% of the total project budget. A case study showed that, although it increased the initial budget by 7.91%, it avoided final cost overruns of up to 229.16%. Four main risk factors were identified in public works: construction, operational, market and financial, and political. To address these, an integrated risk management model and specific public policies are proposed. The study also analyzes 11 types of risks in the bidding phase, offering corresponding corrective actions. These contributions have the potential to substantially improve the performance of construction projects, minimizing cost overruns and delays.